Anionic Extraction for Efficient Recovery of Biobased 2, 3‐Butanediol—A Platform for Bulk and Fine Chemicals. Issue 16 (2nd August 2017) - Drabo, Peter; Tiso, Till; Heyman, Benedikt; Sarikaya, Eda; Gaspar, Paula; Förster, Jochen; Büchs, Jochen; Blank, Lars Mathias; Delidovich, Irina
Abstract: 2, 3‐Butanediol (BDO) presents a promising platform molecule for the synthesis of basic and fine chemicals. Biotechnological production of BDO from renewable resources with living microbes enables high concentrations in the fermentation broth. The recovery of high‐boiling BDO from an aqueous fermentation broth presents a subsequent challenge. A method is proposed for BDO isolation based on reversible complexation with phenylboronate in an anionic complex. BDO can be recovered by back‐extraction into an acidic solution. The composition of the extracted species was determined by NMR spectroscopy, MS, and GC–MS methods. The conditions of extraction and back‐extraction were optimized by using commercial BDO and finally applied to different fermentation broths. Up to 72–93 % BDO can be extracted and up to 80–90 % can be back‐extracted under the optimized conditions. Purified bio‐BDO was used in the presence of sulfuric acid for the synthesis of methyl ethyl ketone, an established organic solvent and discussed tailor‐made biofuel. Abstract : Complex separation : Microbial production of 2, 3‐butanediol based on renewable resources enables high titers; however, the recovery of this hydrophilic high‐boiling compound from aqueous fermentation broths remains challenging. Anionic extraction based on reversible esterification with phenylboronate is proposed for the isolation of 2, 3‐butanediol from aqueous solutions. The recovered bio‐2, 3‐butanediol can be efficiently transformed into methyl ethyl ketone.